Leadership and followership in an organizational change context - Khan, Sajjad Nawaz, 1987-; Busari, Abdul Halim, 1974- (Advances in business strategy and competitive advantage., 2022)
""This book explores the nature of organizational change and how such changes could be managed so that they can provide of both effective leadership and followership"--Provided by publisher"--